FinTech Syariah Dan Implikasinya Terhadap Praktik Akuntansi: Literature Review - Indri Yuliafitri; Nabela Hapsari; Siti Zahrotul Fajriyah (Shofanah Media Berkah, 2025)
The development of financial technology (FinTech) has driven significant transformation in the financial industry, including the Islamic finance sector. Islamic FinTech emerges as an innovation that integrates digital technology with Sharia principles, such as fairness, transparency, and the prohibition of riba. However, the rapid growth of Islamic FinTech raises various implications for accounting practices, particularly in terms of recognition, measurement, presentation, and disclosure of digital-based transactions. This study aims to comprehensively review the development of Islamic FinTech and its implications for accounting practices through a literature review approach. The research method involves reviewing relevant national and international journal articles published within the last five years. The findings indicate that Islamic FinTech influences changes in business models, increases the complexity of digital transaction recording, and requires adjustments in Islamic accounting standards and policies. Furthermore, key challenges identified include regulatory issues, Sharia compliance, data security, and the readiness of accounting human resources. This study is expected to contribute theoretically to the development of Islamic accounting literature and serve as a practical reference for academics, practitioners, and regulators in addressing the dynamics of Islamic FinTech.